Facies Analysis and Thin-Section Petrography for Determining the Lithological Characteristics of Deep-Water Deposits: A Literature Review - Isman Saleh (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
Facies analysis and thin-section petrography are complementary and essential approaches for determining the lithological characteristics of deep-water deposits. Deep-water sediments are formed by diverse depositional processes such as turbidity currents, debris flows, slumps, and pelagic suspension settling, producing a wide range of lithofacies with distinctive textural, compositional, and sedimentary structural attributes. This literature review synthesizes studies that apply facies analysis and thin-section petrography to characterize deep-water deposits across various basins and geological ages worldwide. Field-based facies analysis emphasizes lithology, sedimentary structures, bed geometry, and vertical–lateral facies relationships to reconstruct depositional environments. In contrast, thin-section petrography provides microscopic insights into mineral composition, grain texture, cement types, porosity, and diagenetic features that are not observable in the field. The integration of these methods, often combined with advanced techniques such as XRD, SEM, and geochemical analyses, has proven effective in distinguishing lithofacies, understanding sedimentary processes, and evaluating reservoir quality. The review highlights that grain size, sorting, cement type, pore-throat size, and diagenetic processes are key controls on lithological characteristics and reservoir potential in deep-water systems. Therefore, the combined application of facies analysis and thin-section petrography provides a comprehensive framework for interpreting deep-water sedimentary systems.